2011
DOI: 10.1515/znc-2011-7-814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Salicylic Acid on the Antioxidant Enzyme System and Hydrogen Peroxide Production in Cucumis sativus under Chilling Stress

Abstract: Salicylic acid (SA) is a naturally produced compound and has been implicated to play important roles in defense of plants against diverse biotic and abiotic stresses. To understand how SA functions in the tolerance of cucumber (Cucumis sativus) to chilling stress, endogenous SA levels in two different cultivars with opposite chilling responsiveness were quantified. Membrane integrity, including malondialdehyde (MDA) content and leakage of electrolyte, was also examined in SA-pretreated cucumber plants under ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Mutlu et al ( 2016 ) reported that SA alleviated cold damage in barley subjected to cold stress by stimulating the activities of SOD and POD enzymes. Zhang et al ( 2011 ) reported that SA may influence hydrogen peroxide production in chilled cucumber subjected. This is the first study which proves that SA may stimulate the antioxidant mechanism pathway in rosemary plants subjected to salinity by stimulating antioxidant enzymes activities (SOD, APX, and CAT).…”
Section: Discussionmentioning
confidence: 99%
“…Mutlu et al ( 2016 ) reported that SA alleviated cold damage in barley subjected to cold stress by stimulating the activities of SOD and POD enzymes. Zhang et al ( 2011 ) reported that SA may influence hydrogen peroxide production in chilled cucumber subjected. This is the first study which proves that SA may stimulate the antioxidant mechanism pathway in rosemary plants subjected to salinity by stimulating antioxidant enzymes activities (SOD, APX, and CAT).…”
Section: Discussionmentioning
confidence: 99%
“…SA is necessary for activating plant resistance and plays an important role in plant defence mechanisms 35 37 . Free SA and SA glucoside (SAG, a storage form of SA) are two forms of SA in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of SA and GB in LTRA might contribute to the resistance of tobacco seedlings to low-temperature stress. The beneficial functions of LTRA on tobacco growth might be associated with its SA and GB (Deng et al , 2012; James et al , 2000; Zhang et al , 2011). Our results from Figure 1 supported the above view.…”
Section: Discussionmentioning
confidence: 99%